The Raj in radio wars: BBC Monitoring Reports on Broadcasts for Indian Audiences During the Second World War. Issue 4 (2nd October 2019) - Gupta, Diya
Abstract : This paper draws on broadcast transcripts created by multilingual BBC monitors during the Second World War—which have received little scholarly attention—to consider how conflicting political discourses in wartime India were configured through the airwaves. As both Allied and Axis propaganda vied for the 'hearts and minds' of Indian audiences, how did the subcontinent become a geopolitical hotspot, particularly in 1942 with the threat of Japanese invasion, launch of the anticolonial Quit India movement and Subhas Chandra Bose's nationalist broadcasts from pirate radio stations in Germany? This paper is interested in uncovering how the Indian listener would have 'tuned in', along with understanding monitors' agency in selecting, editing, translating and transcribing these India-oriented transmissions. It seeks to broaden the frames of reference of broadcast history by focusing on non-European/non-US wartime listenership and surveillance, and argues for the value of BBC monitoring transcripts in interrogating the complex relationship between Indian decolonisation and war.